Legalitas Alat Bukti Elektronik dari Hasil Penyadapan dalam Proses Peradilan: ditinjau dari Perspektif Hukum Pidana - Alvieta Alice Reyhanif; Faiza Nisrina (Birokrasi: JURNAL ILMU HUKUM DAN TATA NEGARA, 2024)
In the ever-evolving digital era, information technology has affected various aspects of life, including law enforcement. One important impact is the use of electronic evidence, including wiretap results, in the criminal justice process. Electronic evidence has a crucial role in detecting and proving various criminal acts such as organized crime, corruption, and terrorism. However, the use of wiretap results as evidence often raises debates regarding its legality and validity, especially in the context of potential violations of human rights such as the right to privacy and freedom of communication. In Indonesia, the legality of electronic evidence is regulated in various laws such as the ITE Law and laws that authorize the KPK to conduct wiretapping. This research aims to analyze the legal position and legality of electronic evidence from wiretapping results in the criminal justice process in Indonesia and its implications for the principles of criminal procedure law. The research method used is normative juridical by conducting a literature study. The results showed that although electronic evidence has been substantially recognized, its regulation in the context of procedural law is still not entirely clear. Therefore, more comprehensive and transparent regulations are needed to ensure the realization of a fair judicial process and the protection of human rights.